TiO2 nanotube/g-C3N4/graphene composite as high performance anode material for Na-ion batteries. (February 2021) - Wang, Shuaihao; Zhu, Yuanyi; Jiang, Meng; Cui, Jinlong; Zhang, Yongqiang; He, Wenxiu
Abstract: To improve the electrochemical kinetics and alleviate the structural collapse of TiO2 in the process of charge/discharge, TiO2 nanotubes (TiO2 NT) anchored on a large-area graphitic carbon nitride/reduced graphene oxide (g-C3 N4 /RGO) hybrid nanosheets have been designed by alkaline hydrothermal method. This unique architecture ensures the uniform distribution of TiO2 NT and inhibits the natural tendency to agglomeration of RGO to a large extent. When applied as anode material for Na-ion batteries (NIBs), the resultant sample delivers high reversible capacities of 138.5 mAh g −1 after 244 cycles at 0.1 A g −1 and good rate capability (103.3 mAh g −1 at 0.8 A g −1 ). These excellent sodium storage behaviors are attributed to the double coating effect of g-C3 N4 /RGO nanosheets on TiO2 nanotubes, which can reduce the volume change in the cycle. Therefore, TiO2 nanotubes/graphite phase carbon nitride/graphene composite (TiO2 NT/g-C3 N4 /RGO) should be a promising and attractive NIBs anode material. Highlights: TiO2 NT/g-C3 N4 /RGO composite is prepared by alkaline hydrothermal. The g-C3 N4 /RGO support causes a superior electrochemical performance for sodium storage. The sample retains a capacity of 138.5 mAh g −1 after 244 cycles at 0.1 A g −1 .